Formulation and characterization of Oro Dispersible Films of Etoricoxib using PVA and HPMC - Kumar Vishwakarma, Dhaneshwar; Verma, Navneet; Sahani, Vibhu (Journal of Neonatal Surgery, 2025)
Oral drug delivery is incredibly practical, secure, and cost-effective. In contrast to conventional solid oral dose forms, the current study aims to create oro-dispersible films of etoricoxibe to enhance patient compliance and convenience for both younger and older patients, ultimately leading to greater therapeutic efficacy. Using varying concentrations of PVA and HPMC along with glycerin, sodium starch glycolate, and purified water, different batches of oro-dispersible films of etoricoxibe were prepared by the solvent casting method. The films were then assessed for appearance, weight variation, thickness, folding endurance, drug content, disintegration time and in vitro drug release. The optimized formulation C4 (PVA and HPMC) exhibited acceptable folding endurance (more than 25), least disintegration time (51±1.00 seconds), highest drug content (57±0.89) and highest drug release (100±0.12%) in 10minutes. It can be concluded from the study that the Oro Dispersible Films of etrocoxibe, formulation C5 for sublingual administration can be an optimized formulation.